The relationship between positive mental health and activities of daily living in patients with stroke (Annals of Medical Research, 2023)
Aim: Dependency occurs at various rates in the activities of daily living (ADL) of patients after stroke. Many factors can affect the level of dependence in ADL. The aim of this study is to determine the relationship between positive mental health and ADLs of individuals after stroke.Materials and Methods: This descriptive and correlational study was conducted in the Physical Therapy and Rehabilitation Hospital between May and November 2021. The sample of the study consisted of 84 patients hospitalized for post-stroke rehabilitation. Data were collected through face-to-face interviews with Personal information form, Positive Mental Health Scale, Barthel Activities of Daily Living Index and Instrumental Activities of Daily Living Scale.Results: It was determined that the mean age of the participants was 61.47±9.43 years, 60.7% were male, 88.1% were married, 77.4% were primary school graduates and 48.8% were retired. It was found that 89.3% of the participants were followed up with the diagnosis of hemiplegia, were diagnosed 31.40±40.27 months ago on average. A positive correlation was found between the Barthel ADL and Instrumental ADL scores of the patients and their positive mental health, prosocial attitude, interpersonal relations and autonomy.Conclusion: It was determined that the patients participating in the study were moderately dependent on ADL according to the Barthel ADL and Instrumental ADL indexes. Our study findings show that with the improvement of mental health, an improvement can be achieved in the daily living activities of the patients. Interventions that support autonomy, improve interpersonal relationships, and enable patients to discover areas where they can help others can be recommended in stroke patients.
Keywords: Stroke; Activities of daily living; Positive mental health